Arginine-rich hemp seed globulin-tannic acid non-covalent complexation: Structural compaction, enhanced antioxidant/emulsifying properties, and modulated digestibility - Yu Zhang; Xiao-Dong Tian; Zuo-Xing Di; Hai-Bo Jin; Guang-Xiang He; Suo-He Yang; Rong-Yue Zhang; Lei Ma; Xiao-Yan Guo; Peng-Wei Xu (Food Chemistry, 2026)

Engineering bimetallic Cobalt–Iron glycerate Co-Catalysts on bismuth vanadate for improved charge transfer and photoelectrochemical catalytic water oxidation - Tsung-Rong Kuo; He-Jin Li; Kai-Jie Chuang; Chutima Kongvarhodom; Sibidou Yougbaré; Muhammad Saukani; Hung-Ming Chen; Lu-Yin Lin (Fuel, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

The synthesis of alkaline earth metal-organic framework based on asymmetric triazine hexacarboxylic acid and iodine capture performance - Shao Bin Xu; He Qun Cai; Rong Huo; Ting Zhang; Jing Jin; Yong Heng Xing; Feng Ying Bai (Environmental Research, 2026)

Biochar–bentonite composite enabling antibiotic removal and greenhouse gas mitigation in waters - Yan Sun; Xiang Jia; Le Dai; Wei Ding; Yongjie Wang; Jin Zhang; Huan He; Nan Rong; Pei Lei (Chemical Engineering Journal, 2026)

An Indicator System for Evaluating the Powerhouse of Meteorological Science and Technology: Design and Preliminary Application - Chaolin Zhang; Xudong Liang; Min Wen; Jianjun He; Wenjuan Zhang; Chang Liu; Qing Sun; Rong Yu; Xiaolu Yan; Zhu Zhang; Qihua Jin; Aili Shi; et al. (Journal of Meteorological Research, 2026)

Effects of GIAHS conservation on agricultural landscape and ecological sustainability in heritage sites: evidence from the Yuanyang Hani Rice Terraces - Jin-Rong Zhang; Hong-Bo Li; He-Ping Yang; Meng-Na Qi (Environment, Development and Sustainability, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

A novel phytoformula targeting lipid peroxidation inhibition attenuates UV-induced skin photoaging - Ling-Ping Wu; Wei Chen; Qian-Pei Lin; Shi-Yun Feng; Jin Dai; Qiong-Yi Zhang; Wen-Yi Chen; Hiroshi Kurihara; Xiao-Min Li; Shu-Hua Ouyang; Yi-Fang Li; Rong-Rong He (PharmaNutrition, 2026)

Indole metabolites produced by Lactobacillus acidophilus impedes bisphenol F- aryl hydrocarbon receptor interaction and ameliorates bisphenol F induced depression-like changes - Miaoyang Hu; Ayiguzaili Manglike; Xiaozhu Li; Jin Wei; Xinyu Lou; Jing Liu; Zhiru Tang; Weiping He; Guixiang Ji; Wenjuan Wang; Tengfei Ma; Rong Gao; et al. (Journal of Hazardous Materials, 2026)

Host switching and successive subculturing drive adaptive responses in Liriomyza sativae - Yang Gao; Wei He; Ming Zhang; Hai-Nuo Hong; Jin Wang; Ying Zhou; Zeng‑Rong Zhu (Journal of Pest Science, 2026)

Bridging cortical intentions: brain–computer interfaces for spinal cord injury recovery - Xuantao Hu; Jiale He; Na Li; Jian Mo; Senyu Yao; Yubao Lu; Mudan Huang; Pan Jiang; Mao Pang; Lei He; Jin Gong; Zifeng Liu; et al. (Science Bulletin, 2026)

Lengthening vegetation carbon turnover time across China’s forests - Rong Ge; Xiaoli Ren; Honglin He; Guirui Yu; Li Zhang; Qian Xu; Mengyu Zhang; Shilong Piao; Kailiang Yu; Mathew Williams; Xiaobo Zhu; Shiyong Yu; et al. (Science Bulletin, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Mechanoluminescent Janus architecture for stimulus-responsive photodynamic therapy - Rong-Kai Du; Xu-Lin He; Qing-Qing Jin; Hong Liang; Tai-Zhong Xiao; Lei Zhong; Jun-Cheng Zhang; Tian-Ying Sun; Lei Zhou; Ming-Mei Wu (Chemical Engineering Journal, 2026)

Screening of Fecal Bacteroides Strains and Discovery of Bacteroides eggerthii S13-F8 with Protective Effects Against Chemotherapy-Induced Diarrhea - Yi Zhao; Zhengqun Dai; Yanmei Lang; Rui Li; Hongyu Zheng; Jiajia Mi; Xiu He; Jin Liu; Rong Xiang; Xueran Mei; Yang Liu; Yantang Wang; et al. (Probiotics and Antimicrobial Proteins, 2026)

Navigating the lunar frontier: one hundred landing sites at the south pole for future mission challenges - Yongjiu Feng; Pengshuo Li; Haoteng Li; Yan Liu; Mengrong Xi; Rong Wang; Shurui Chen; Panli Tang; Yuze Cao; Qian Huang; Qionghua You; Shijie Liu; et al. (Science Bulletin, 2025)

Isolation of pentasaccharide resin glycosides from the whole plants of Ipomoea biflora and their cytotoxic activities - Jin-Ping Gu; Tian-Zi Qi; Dong-Rong Zhu; Xu-Jia He; Su-Peng Guo; Xin Lan; Hong Gu; Jia-Lie Luo; Min Yang; Yu-Cheng Gu; Wen-Li Wang; Guang-Tong Chen; et al. (Phytochemistry, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Pyroptosis was suppressed by 20-hydroxyecdysone through Lin28b-mediated let-7d in vascular endothelial cells - Danli Chen; Jianjun Yang; Lingxuan Ren; Zihan Zheng; Zhen Jin; Jiazheng Wen; Jianyu He; Rongcheng Ding; Jianjiang Wang; Rong Lin; Qiang Song (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Synergistic enhancement of flame retardancy, mechanical properties, dimensional stability, and mold resistance in bamboo via silica mineralization and hydrophobic treatment - Lu He; Gege Bao; Xi Yu; Xiaofeng Zhang; Xiaobei Jin; Zixuan Yu; Rong Zhang; Daochun Qin (Chemical Engineering Journal, 2025)

A Global Synthesis of How Plants Respond to Climate Warming From Traits to Fitness - Pengyan Jia; Rong Zhang; Bernhard Schmid; Han Wang; Jin‐Sheng He; Jiaxi Liu; Sijie Liu; Sipeng Jian; Yanhao Feng (Ecology Letters, 2025)
Despite intensive research, our understanding of how plants respond to warming by coordinating their full arsenal of traits to adjust fitness is lacking. To fill this gap, we applied a trait‐based framework with three clusters (two functional clusters: “carbon‐fixation rate” and “carbon‐fixation area”; a third cluster: “total carbon fixation”) to a global dataset compiled from 572 studies of warming experiments with 677 species and a comprehensive list of traits and fitness components. The pairwise correlation analysis complemented with SEM and PCA showed that plants increased biomass (the core variable in the third cluster) under warming by coordinating satellite traits in two functional clusters to adjust their core traits, net photosynthesis rate and total leaf area, respectively. In particular, the trait coordination was characterised by the maintenance of net photosynthesis rate and the increase of total leaf area, which was robust across ecological contexts although warming responses of the variables per se displayed context‐dependences. Moreover, the trade‐offs between biomass and reproduction (itself bearing mass vs. number trade‐offs) in their warming responses scaled the coordination to enhance fitness except in the contexts where reproduction was reduced. These findings could help explain and predict plant form and function in a warming world.

Efficient uranium(VI) recovery from fluorinated wastewater via deferiprone ligand complexation - Juanlong Li; Yezi Hu; Zewen Shen; Huihui Jin; Rong He; Wenkun Zhu; Guixia Zhao; Zhuoyu Ji; Bin Ma; Xiangke Wang (Water Research, 2025)

Effects of microclimatic conditions and urban building configurations on aerodynamic characteristics and health risks of bioaerosols: Insights from idealized urban models - Zhijian Dong; Zhijian Liu; Chenxing Hu; Chenglin Ye; Yongjun Jin; Haiyang Liu; Rui Rong; Yuchen He; Li Chen; Chuanchen Li; Yaolong Shi; Yufeng Su (Sustainable Cities and Society, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

The Role of the Intestinal Flora and Its Derivatives in Neurocognitive Disorders: A Narrative Review from Surgical Perspective - Jian Huang; Tian-Shou Qin; Yun Bo; Yu-Jin Li; Rong-Sheng Liu; Yang Yu; Xiao-Dong Li; Jin-Can He; Ai-Xin Ma; Da-Peng Tao; Wen-Jun Ren; Jun Peng (Molecular Neurobiology, 2025)
Perioperative neurocognitive dysfunction is a significant concern for population health, impacting postoperative recovery and increasing the financial burden on patients. With an increasing number of surgical procedures being performed, the prevention and management of perioperative neurocognitive dysfunction have garnered significant attention. While factors such as age, lifestyle, genetics, and education are known to influence the development of cognitive dysfunction, recent research has highlighted the role of the gut microbiota in neurological health. An increased abundance of pro-inflammatory gut microbiota can trigger and worsen neuroinflammation, neuronal cell damage, and impaired cellular autophagy. Moreover, the inflammation-promoting gut microbiota can disrupt immune function, impair neuroautophagy, and affect the production and circulation of extracellular vesicles and neurotransmitters. These factors collectively play a role in the onset and advancement of cognitive impairment. This narrative review delves into the molecular mechanisms through which gut microbiota and their derivatives contribute to cognitive impairment, focusing on the impact of anesthesia surgery, changes in gut microbial populations, and perioperative cognitive impairment associations. The study suggests that alterations in the abundance of various bacterial species and their metabolites pre- and post-surgery may be linked to postoperative cognitive impairment. Furthermore, the potential of probiotics or prebiotics in addressing cognitive impairment is discussed, offering a promising avenue for investigating the treatment of perioperative neurocognitive disorders.

PM2.5 constituents associated with mortality and kidney failure in childhood-onset lupus nephritis: A 19-year cohort study - Guohua He; Yaqi Wang; Cheng Cheng; Jianhui Guo; Zhilang Lin; Ziyun Liang; Bei Jin; Liyuan Tao; Liping Rong; Lizhi Chen; Tianxin Lin; Yining Hua; et al. (Science of The Total Environment, 2024)

Optimizing shrimp nutrition and health: ginseng saponins as functional additives in low-fishmeal diets on Litopenaeus vannamei - Sihan Lin; Rong Yao; Xin Cui; Yucai Guo; Denghui Hu; Bin Zhou; Zhaobin Zhou; Xuanshu He; Zhihong Liao; Beiping Tan; Jin Niu (Frontiers in Marine Science, 2024)
The research investigated the nutritional physiology effect of ginseng saponins on Litopenaeus vannamei ( L. vannamei ) under low-fishmeal diets. In total, five experimental groups were arranged, with 21% fishmeal (high-fishmeal) serving as the positive control (PC), 11% fishmeal (low-fishmeal) serving as the negative control (NC), and 11% fishmeal serving as the addition in all three other groups. Similarly, ginseng saponins (GSP, purity of 2%) were added in the order of 0.1%, 0.3%, and 0.5% (GSP0.1, GSP0.3, and GSP0.5), with an 8-week growth cycle. Both GSP0.1 and GSP0.3 showed significantly higher growth performance (final body weight, FBW; weight gain rate, WGR; specific growth rate, SGR) than the NC group, but significantly lower growth performance than the PC group ( P <0.05). However, it was found that there was no significant difference in the body composition of the whole shrimp between the experimental groups. Compared to the PC group, the GSP0.3 group exhibited significantly elevated levels of antioxidant enzymes, total antioxidant capacities (T-AOC), superoxide dismutase (SOD), and glutathione peroxidase (GSH-Px) ( P <0.05). Additionally, significant differences were observed between the PC and GSP0.3 groups regarding the expression levels of sod , cat , and gsh-px (P<0.05). And there was a better morphological organization of shrimp hepatopancreas in the GSP0.3 group than in all other groups. In comparison with the PC group, there was no significant difference in shrimp survival rates after ammonia nitrogen stress with ginseng saponins added ( P >0.05). Whereas, in terms of the relative expression levels of the corresponding genes, in shrimp of the GSP0.3 group, the relative expression of antioxidant-related genes sod , cat , and gsh-px were significantly higher than that of the PC group ( P <0.05). Caspase3 and p53 , along with bcl-2 and bax , were found to be significantly more expressed in shrimp of the GSP0.3 group than in all other groups ( P <0.05). These findings imply that in addition to improving growth performance, adding ginseng saponins at a concentration of 11% fishmeal could improve the antioxidant capacity of L. vannamei as well as its resistance to stress. Therefore, ginseng saponins can be utilized as a functional additive to increase L. vannamei growth performance, enhance antioxidant capacity, and reduce stress in low-fishmeal diets, 0.3% of ginseng saponins is optimal.

Short-term effects of ambient nitrogen dioxide on medical emergency calls for epileptic seizures: A time-series study - Yijie Wang; Fei Wang; Rong He; Yiming Wang; Yumin Liu; Xiaoqing Jin (International Journal of Biometeorology, 2024)

Assessment of the hormesis effect and toxic damage of short-term low-dose aflatoxin B1 in grass carp (Ctenopharyngodon idellus) - Jin-long Li; Jia-rong Guo; Pei Wang; Jun-zhi Zhang; Zhi-gang He; Jin-long Wang; Yi Hu (Frontiers in Marine Science, 2024)
The present study was conducted to evaluate the hormesis and toxicity of short-term low-dose aflatoxin B1 in grass carp ( Ctenopharyngodon idellus ). Triplicate isonitrogenous and isocaloric aflatoxin B1 diets—CD (control, 0 ug/kg), D1 (20 ug/kg), and D2 (500 ug/kg)—were prepared and fed to grass carp with an initial mean body weight of (15.2 ± 0.1) g for 56 days. The results showed that the weight gain rate and specific growth rate of grass carp fed diet D2 were significantly higher, and the feed coefficient and crude fat content of the whole body were significantly lower ( P < 0.05) compared with those fed diet CD. Serum superoxide dismutase content of grass carp fed D1 diet increased significantly ( P < 0.05) with an increasing dose of aflatoxin B1, but when the dose reached 500 ug/kg (D2), serum superoxide dismutase, complement C3, and immunoglobulin M of grass carp decreased significantly ( P < 0.05), while malondialdehyde increased significantly ( P < 0.05). After short-term feeding of aflatoxin B1-containing diets (D1 and D2), liver body index, visceral body index, serum total cholesterol, triglyceride, and urea nitrogen content of grass carp increased significantly ( P < 0.05), total bile acid secretion decreased significantly ( P < 0.05), and structural damages such as increase in vacuoles, organizational structure loosening, and nucleus translocation were observed in the liver. Meanwhile, liver function indexes such as serum alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase increased significantly with the increase of aflatoxin B1 dose ( P < 0.05). In addition, the height of intestinal villi, crypt depth, villus–crypt ratio, and tubular cell number, as well as the content of trypsin and lipase activities in the intestine of grass carp in the D2 group, were significantly higher than those in the CD group ( P < 0.05). In conclusion, after a short-term intake of low doses of aflatoxin B1 (≤500 ug/kg), the toxicological damage of aflatoxin B1 was pronounced, although it produced a certain degree of hormesis on the growth performance and intestinal structure and function of grass carp. At a dose of 20 ug/kg, the non-specific immune system and liver structure and function of grass carp showed obvious toxic damage.

Sustainable design of photo-Fenton-like oxidation process in actual livestock wastewater through the highly dispersed FeCl3 anchoring on a g-C3N4 substrate - Yanfang Feng; Yunyi Liang; Chenman Ding; Yue Jiang; Hongmei Jin; Shaopeng Rong; Jun Wu; Shiying He; Changlei Xia; Lihong Xue (Water Research, 2024)

Modeling the long-range transmission of airborne bioaerosol releases in a high-density urban environment - Zhijian Dong; Zhijian Liu; Chenxing Hu; Yongjun Jin; Chenglin Ye; Yuchen He; Rui Rong (Urban Climate, 2024)

Recycling drinking water treatment sludge in construction and building materials: A review - Zhi-hai He; Bin Wang; Jin-yan Shi; Hui Rong; Hong-yu Tao; Ahmed Salah Jamal; Xu-dong Han (Science of The Total Environment, 2024)

Upcycling textile sludge into magnesium oxychloride cement: Physical properties, microstructure, and leaching behavior - Zhi-hai He; Ya-qian Ni; Jin-yan Shi; Hui Rong; Hong-yu Tao; Ahmed Salah Jamal (Science of The Total Environment, 2024)

A green and eco-friendly method to enhance Bamboo flame resistance via calcium alginate assisted in-situ mineralization of hydroxyapatite - Lu He; Gege Bao; Xi Yu; Xiaofeng Zhang; Xiaobei Jin; Zixuan Yu; Ying He; Rong Zhang; Daochun Qin (Chemical Engineering Journal, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Tree species mixture effect on extracellular enzyme kinetics varies with enzyme type and soil depth in subtropical plantations - Xue-Li Jiang; Rong Mao; Zhong-Liang Li; Fu-Sheng Chen; Bin Xu; Jin He; Yu-Xin Huang; Xiang-Min Fang (Plant and Soil, 2023)

Improving Blood Monocyte Energy Metabolism Enhances Its Ability to Phagocytose Amyloid-β and Prevents Alzheimer’s Disease-Type Pathology and Cognitive Deficits - Zhi-Hao Liu; Yu-Di Bai; Zhong-Yuan Yu; Hui-Yun Li; Jie Liu; Cheng-Rong Tan; Gui-Hua Zeng; Yun-Feng Tu; Pu-Yang Sun; Yu-Juan Jia; Jin-Cai He; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2023)

Effects of Different Conditioners on Humus Composition and Humic Acid Structural Characteristics in Black Soil Under the Combined Application of Pig Manure and Straw - Shuang Zheng; Jing-Gui Wu; Jin-Rong Li; Juan Hu; Li He (Journal of Soil Science and Plant Nutrition, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

G-quadruplex based biosensors for the detection of food contaminants - Rong Du; Xiebingqing Yang; Ping Jin; Yahui Guo; Yuliang Cheng; Hang Yu; Yunfei Xie; He Qian; Weirong Yao (Critical Reviews in Food Science and Nutrition, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

The early Late Triassic Yumen mafic rocks in the eastern Tethyan Himalaya: A record of the progressive opening of the Yarlung Zangbo Neo-Tethyan Ocean - Wei-Liang Liu; Zhong-Xi Xia; Yun Zhong; Chris Yakymchuk; Zhou-Rong Cai; He Xiao; Xing Liao; Chi Yan; Ru-Xin Ding; Jin-Nan Liu (Lithos, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Retraction Note: Emerging protective roles of shengmai injection in septic cardiomyopathy in mice by inducing myocardial mitochondrial autophagy via caspase-3/Beclin-1 axis - Yan Cao; Xiaotong Han; Hongwei Pan; Yu Jiang; Xiang Peng; Weiwei Xiao; Jingjing Rong; Fang Chen; Jin He; Lianhong Zou; Yi Tang; Yanfang Pei; et al. (Inflammation Research, 2023)

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

Short-term exposure to air pollution is an emerging but neglected risk factor for schizophrenia: A systematic review and meta-analysis - Rong Song; Li Liu; Ning Wei; Xuanxuan Li; Jintao Liu; Jiajun Yuan; Shuangshuang Yan; Xiaoni Sun; Lu Mei; Yunfeng Liang; Yuxuan Li; Xiaoyu Jin; et al. (Science of The Total Environment, 2023)

A strategy for screening and identification of new amino acid-conjugated bile acids with high coverage by liquid chromatography-mass spectrometry - Yan-Zhen Wang; Peng-Cheng Mei; Pei-Rong Bai; Na An; Jin-Gang He; Jie Wang; Quan-Fei Zhu; Yu-Qi Feng (Analytica Chimica Acta, 2023)

Analysis of the effect of seasonal changes on sensitive parameters of LAI-based Penman–Monteith evapotranspiration model based on particle swarm algorithm - Hao Duan; Xin He; Hongli Zhao; Xiaohui Jin; Haowei Xu; Rong Wang (Acta Geophysica, 2022)

Complex impacts of hydraulic fracturing return fluids on soil microbial community respiration, structure and functional potentials - Cheng Zhong; Camilla L. Nesbø; Konstantin von Gunten; Yifeng Zhang; Xiaoqing Shao; Rong Jin; Kurt O. Konhauser; Greg G. Goss; Jonathan W. Martin; Yuhe He; Pei‐Yuan Qian; Brian D. Lanoil; et al. (Environmental Microbiology, 2022)
Summary The consequences of soils exposed to hydraulic fracturing (HF) return fluid, often collectively termed flowback and produced water (FPW), are poorly understood, even though soils are a common receptor of FPW spills. Here, we investigate the impacts on soil microbiota exposed to FPW collected from the Montney Formation of western Canada. We measured soil respiration, microbial community structure and functional potentials under FPW exposure across a range of concentrations, exposure time and soil types (luvisol and chernozem). We find that soil type governs microbial community response upon FPW exposure. Within each soil, FPW exposure led to reduced biotic soil respiration, and shifted microbial community structure and functional potentials. We detect substantially higher species richness and more unique functional genes in FPW‐exposed soils than in FPW‐unexposed soils, with metagenome‐assembled genomes (e.g. Marinobacter persicus ) from luvisol soil exposed to concentrated FPW being most similar to genomes from HF/FPW sites. Our data demonstrate the complex impacts of microbial communities following FPW exposure and highlight the site‐specific effects in evaluation of spills and agricultural reuse of FPW on the normal soil functions.

Effects of Dietary Rhodobacter sphaeroides Protein Substitution of Fishmeal and Coenzyme Q10 Supplementation on Growth Performance, Intestinal Microbiota and Stress Tolerance of Litopenaeus vannamei in Acute Low Salinity - Zhihong Liao; Yangyang Gong; Ziqiao Wang; Yingjie Wang; Rong Yao; Mengdie Chen; Dan Wei; Wei Zhao; Xuanshu He; Jin Niu (Frontiers in Marine Science, 2022)
A 56-day culture experiment followed by an acute low salinity challenge was conducted to evaluate the effects of Rhodobacter sphaeroides protein (RSP) substitution of fishmeal and Coenzyme Q10 (CoQ10) supplementation on growth performance, intestinal microbiota and compressive capacity of Litopenaeus vannamei ( L. vanname i). Four experimental diets were formulated: FM diet (20% fishmeal), RSP diet (20% RSP instead of 20% fishmeal), CoQ10 diet (20% fishmeal supplemented with CoQ10 at 0.08 g kg –1 ), RSP + CoQ10 diet (20% RSP supplemented with CoQ10 at 0.08 g kg –1 ). The obtained results were denoted that L. vannamei fed CoQ10 diet could improve growth performance (weigh gain and specific growth rate), condition factor and crude lipid, and decrease hepatosomatic index, but no differences were found in survival rates. High throughput sequencing on intestinal microbiota indicated that intestinal microbiota of L. vannamei consisted mainly of Proteobacteria and Firmicutes . The species richness of the RSP diet was remarkably higher than that of the other diets. Moreover, the presence of RSP and CoQ10 may improve intestinal homeostasis by inhibiting the propagation of Vibrio . Compared to FM diet and RSP diet, supplementation of CoQ10 significantly improved the compressive capacity of L. vannamei against the acute low salinity challenge, as indicated by higher survival rates as well as higher activities of T-AOC and higher transcript levels of SOD , HSP70 , and Relish gene. Our findings demonstrated that RSP could serve as a novel FM and CoQ10 could serve as a prospective feed additive to help L. vannamei to overcome environmental stresses.

The chemical profile and biological activity of different extracts of Sapindus mukorossi Gaertn. against Cutibacterium acnes - Min-Ping Wei; Jin-Dan Qiu; Lu Li; Yun-Fei Xie; Ya-Hui Guo; Hang Yu; Yu-Liang Cheng; He Qian; Wei-Rong Yao (Natural Product Research, 2021)

Retrospective surveillance of porcine circovirus 4 in pigs in Inner Mongolia, China, from 2016 to 2018 - Zhuo Ha; Chengdong Yu; Changzhan Xie; Guanyu Wang; Ying Zhang; Pengfei Hao; Jinfeng Li; Zhuoxin Li; Yanwei Li; Fulong Rong; Fulong Nan; He Zhang; et al. (Archives of Virology, 2021)

Transcutaneous Auricular Vagus Nerve Stimulation: From Concept to Application - Yu Wang; Shao-Yuan Li; Dan Wang; Mo-Zheng Wu; Jia-Kai He; Jin-Ling Zhang; Bin Zhao; Li-Wei Hou; Jun-Ying Wang; Lei Wang; Yi-Fei Wang; Yue Zhang; et al. (Neuroscience Bulletin, 2021)

Genome sequencing and functional annotation of Bacillus sp. strain BS-Z15 isolated from cotton rhizosphere soil having antagonistic activity against Verticillium dahliae - Zhong-Yi Chen; Xieerwanimu Abuduaini; Nuramina Mamat; Qi-Lin Yang; Meng-Jun Wu; Xin-Rui Lin; Ru Wang; Rong-Rong Lin; Wei-Jun Zeng; Huan-Chen Ning; He-Ping Zhao; Jin-Yu Li; et al. (Archives of Microbiology, 2021)

Purinergic signaling as a basis of acupuncture-induced analgesia - Jin-Rong He; Shu-Guang Yu; Yong Tang; Peter Illes (Purinergic Signalling, 2020)
This review summarizes experimental evidence indicating that purinergic mechanisms are causally involved in acupuncture (AP)-induced analgesia. Electroacupuncture (EAP) and manual AP release at pain-relevant acupoints ATP which may activate purinergic P2X receptors (Rs) especially of the P2X3 type situated at local sensory nerve endings (peripheral terminals of dorsal root ganglion [DRG] neurons); the central processes of these neurons are thought to inhibit via collaterals of ascending dorsal horn spinal cord neurons, pain-relevant pathways projecting to higher centers of the brain. In addition, during AP/EAP non-neuronal P2X4 and/or P2X7Rs localized at microglial cells of the CNS become activated at the spinal or supraspinal levels. In consequence, these microglia secrete bioactive compounds such as growth factors, cytokines, chemokines, reactive oxygen, and nitrogen species, which modulate the ascending neuronal pathways conducting painful stimuli. Alternatively, ATP released at acupoints by AP/EAP may be enzymatically degraded to adenosine, stimulating in loco presynaptic A1Rs exerting an inhibitory influence on the primary afferent fibers (the above mentioned pain-sensing peripheral terminals of DRG neurons) which thereby fail to conduct action potentials to the spinal cord dorsal horn. The net effect of the stimulation of P2X3, P2X4, P2X7, and A1Rs by the AP/EAP-induced release of ATP/adenosine at certain acupoints will be analgesia.

Serum Uric Acid Levels and Risk of Intracranial Atherosclerotic Stenosis: A Cross-Sectional Study - Lin Li; Jun-Xia Zhu; Xiao-He Hou; Ya-Hui Ma; Wei Xu; Chen-Chen Tan; Fu-Rong Sun; Hong-Qi Li; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Elevated Hs-CRP Levels Are Associated with Higher Risk of Intracranial Arterial Stenosis - Bing-Jie Su; Yi Dong; Chen-Chen Tan; Xiao-He Hou; Wei Xu; Fu-Rong Sun; Mei Cui; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

RETRACTED ARTICLE: Emerging protective roles of shengmai injection in septic cardiomyopathy in mice by inducing myocardial mitochondrial autophagy via caspase-3/Beclin-1 axis - Yan Cao; Xiaotong Han; Hongwei Pan; Yu Jiang; Xiang Peng; Weiwei Xiao; Jingjing Rong; Fang Chen; Jin He; Lianhong Zou; Yi Tang; Yanfang Pei; et al. (Inflammation Research, 2020)

Angiogenesis in pancreatic cancer: current research status and clinical implications - Shuo Li; Hua-Xiang Xu; Chun-Tao Wu; Wen-Quan Wang; Wei Jin; He-Li Gao; Hao Li; Shi-Rong Zhang; Jin-Zhi Xu; Zi-Hao Qi; Quan-Xing Ni; Xian-Jun Yu; et al. (Angiogenesis, 2019)

Frond transformation system mediated by Agrobacterium tumefaciens for Lemna minor - Gui-Li Yang; Yang Fang; Ya-Liang Xu; Li Tan; Qi Li; Yang Liu; Fan Lai; Yan-Ling Jin; An-Ping Du; Kai-Ze He; Xin-Rong Ma; Hai Zhao (Plant Molecular Biology, 2018)

Soil nutrients in relation to vertical roots distribution in the riparian zone of Three Gorges Reservoir, China - Rong-hua Zhong; Jin-ming Hu; Yu-hai Bao; Fei Wang; Xiu-bin He (Journal of Mountain Science, 2018)

Discovery of a novel multifunctional carbazole–aminoquinoline dimer for Alzheimer's disease: copper selective chelation, anti-amyloid aggregation, and neuroprotection - Xiao Zhang; Ying Wang; Sheng-nan Wang; Qiu-he Chen; Ya-lin Tu; Xiao-hong Yang; Jing-kao Chen; Jin-wu Yan; Rong-biao Pi; Yan Wang (Medicinal Chemistry Research, 2018)

NaCl stress induces CsSAMs gene expression in Cucumis sativus by mediating the binding of CsGT-3b to the GT-1 element within the CsSAMs promoter - Li-Wei Wang; Mei-Wen He; Shi-Rong Guo; Min Zhong; Sheng Shu; Jin Sun (Planta, 2017)

The dynamics of landscape-scale ecological connectivity based on least-cost model in Dongshan Island, China - Li-yun Wu; Dong-jin He; Wei-bin You; Zhi-rong Ji; Yong Tan; Li-li Zhao (Journal of Mountain Science, 2017)

Estimation of soil reinforcement by the roots of four post-dam prevailing grass species in the riparian zone of Three Gorges Reservoir, China - Rong-hua Zhong; Xiu-bin He; Yu-hai Bao; Qiang Tang; Jin-zhang Gao; Dan-dan Yan; Ming-feng Wang; Yu Li (Journal of Mountain Science, 2016)

Determination and Method Validation of the New Sulfone Fungicide 2-(4-Fluorophenyl)-5-Methylsulfonyl-1,3,4-Oxadiazole in Tomato and Soil by UPLC in Field Trial Samples from Guizhou Province, China - Rong Linghu; Mingjiao Jin; Sizhu Pan; Jing Zhang; Mingming Tang; Jin He; Kankan Zhang; Deyu Hu (Bulletin of Environmental Contamination and Toxicology, 2015)

Anti-herpes simplex virus activity of polysaccharides from Eucheuma gelatinae - Fujun Jin; Cuiqin Zhuo; Zhe He; Huailin Wang; Wei Liu; Rong Zhang; Yifei Wang (World Journal of Microbiology and Biotechnology, 2015)

Effects of land cover on soil organic carbon stock in a karst landscape with discontinuous soil distribution - Xiang-bi Chen; Hua Zheng; Wei Zhang; Xun-yang He; Lei Li; Jin-shui Wu; Dao-you Huang; Yi-rong Su (Journal of Mountain Science, 2014)

Isolation from Proteus mirabilis of a novel class I 5-enopyruvylshikimate-3-phosphate synthase with glyphosate tolerance in transgenic Arabidopsis thaliana - Yong-Sheng Tian; Xiao-Fen Jin; Jing Xu; Jing Han; Wei Zhao; Xiao-Yan Fu; Ri-He Peng; Rong-Tan Wang; Quan-Hong Yao (Acta Physiologiae Plantarum, 2014)

Association of single-nucleotide polymorphisms in the STAT3 gene with autoimmune thyroid disease in Chinese individuals - Ling Xiao; Fatuma-Said Muhali; Tian-tian Cai; Rong-hua Song; Renming Hu; Xiao-hong Shi; Wen-juan Jiang; Dan-Feng Li; Shuang-tao He; Jian Xu; Jin-an Zhang (Functional & Integrative Genomics, 2013)

Persistence and intergenerational transmission of differentially expressed genes in the testes of intracytoplasmic sperm injection conceived mice - Li-ya Wang; Ning Wang; Fang Le; Lei Li; Le-jun Li; Xiao-zhen Liu; Ying-ming Zheng; Hang-ying Lou; Xiang-rong Xu; Xiao-ming Zhu; Yi-min Zhu; He-feng Huang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Tectonic mechanism of the Suining (Ms5.0) earthquake, center of Sichuan Basin, China - Rong-jun Zhou; Yong Li; Laurence Svirchev; Yong-jiu Zhang; Deng-fa He; Yu-lin He; Pei-lin Zhao; Zan-jun Wang; Feng Long; Jin-rong Su; Shi-yuan Wang; Ming-jian Liang; et al. (Journal of Mountain Science, 2013)

A molecular mechanism underlying ovarian dysfunction of polycystic ovary syndrome: hyperandrogenism induces epigenetic alterations in the granulosa cells - Fan Qu; Fang-Fang Wang; Rong Yin; Guo-Lian Ding; Mohamed El-prince; Qian Gao; Bi-Wei Shi; Hui-Hui Pan; Yi-Ting Huang; Min Jin; Peter C. K. Leung; Jian-Zhong Sheng; et al. (Journal of Molecular Medicine, 2012)

Association between ATM 5557G>A polymorphism and breast cancer risk: a meta-analysis - Chen Mao; Vincent C. H. Chung; Ben-Fu He; Rong-Cheng Luo; Jin-Ling Tang (Molecular Biology Reports, 2012)

Normal epigenetic inheritance in mice conceived by in vitro fertilization and embryo transfer - Lei Li; Fang Le; Li-ya Wang; Xiang-rong Xu; Hang-ying Lou; Ying-ming Zheng; Jiang-zhong Sheng; He-feng Huang; Fan Jin (Journal of Zhejiang University-SCIENCE B, 2011)

Methylobacterium soli sp. nov. a methanol-utilizing bacterium isolated from the forest soil - Yan-Ru Cao; Qian Wang; Rong-Xian Jin; Shu-Kun Tang; Yi Jiang; Wen-Xiang He; Hang-Xian Lai; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2011)

Over-expression of ThpI from Choristoneura fumiferana enhances tolerance to cold in Arabidopsis - Bo Zhu; Ai-Sheng Xiong; Ri-He Peng; Jing Xu; Xiao-Fen Jin; Xiu-Rong Meng; Quan-Hong Yao (Molecular Biology Reports, 2010)

Induction of cytochrome P450 2B6 activity by the herbal medicine baicalin as measured by bupropion hydroxylation - Lan Fan; Jin-Chao Wang; Feng Jiang; Zhi-Rong Tan; Yao Chen; Qing Li; Wei Zhang; Guo Wang; He-Ping Lei; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

BRD2 is one of BRD7-interacting proteins and its over-expression could initiate apoptosis - Ming Zhou; Xiao-Jie Xu; Hou-De Zhou; Hua-Ying Liu; Jia-Jin He; Xiao-Ling Li; Cong Peng; Wei Xiong; Song-Qing Fan; Jian-Hong Lu; Jue Ouyang; Shou-Rong Shen; et al. (Molecular and Cellular Biochemistry, 2006)

Genetic spatial clustering: significant implications for conservation of wild soybean (Glycine soja: Fabaceae) - Yan Jin; Tianhua He; Bao-Rong Lu (Genetica, 2006)

Tissue distribution of the secretory protein, SPLUNC1, in the human fetus - Hou-De Zhou; Song-Qin Fan; Jin Zhao; Dong-Hai Huang; Ming Zhou; Hua-Ying Liu; Zhao-Yang Zeng; Yi-Xing Yang; He Huang; Xiao-Ling Li; Shou-Rong Shen; Gui-Yuan Li (Histochemistry and Cell Biology, 2006)

OsGLU1, A Putative Membrane-bound Endo-1,4-ß-D-glucanase from Rice, Affects Plant Internode Elongation - Hua-Lin Zhou; Si-Jie He; Yang-Rong Cao; Tao Chen; Bao-Xing Du; Cheng-Cai Chu; Jin-Song Zhang; Shou-Yi Chen (Plant Molecular Biology, 2006)

Environmental evolution of ordos desert in china since 1.1Ma B.P. as indicated by Yulin stratigraphical section and its grain-size analysis results - Bao-sheng Li; Shang-yu Gao; Guang-rong Dong; He-ling Jin (Chinese Geographical Science, 2005)